Plant Health Status Affects the Functional Diversity of the Rhizosphere Microbiome Associated With Solanum lycopersicum - Adedayo, Afeez Adesina; Fadiji, Ayomide Emmanuel; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2022)
The microorganisms inhabiting soil perform unique functions in the growth and development of plants. However, little is known about how plant health status affects their potential functions. We examined the functional diversity of the microbiome inhabiting the rhizosphere of powdery mildew diseased and healthy tomato plants alongside the bulk soils in South Africa’s Northwest Province employing a shotgun metagenomics approach. We envisaged that the functional categories would be abundant in the healthy rhizosphere (HR) of the tomato plant. We collected soil from the rhizosphere of healthy, powdery mildew diseased tomato plant (DR), and bulk soil (BR). After that, their DNA was extracted. The extracted DNA was subjected to shotgun metagenomic sequencing. Our result using the SEED subsystem revealed that a total of fifteen (15) functional categories dominated the healthy rhizosphere, seven (7) functional categories dominated the diseased rhizosphere. At the same time, six (6) functions dominated the bulk soil. Alpha (α) diversity assessment did not reveal a significant difference (p > 0.05) in all the soil samples, but a considerable difference was observed for beta (β) diversity (P=0.01). The functional categories obtained in this research were highly abundant in HR. This shows that the functions of the rhizosphere microbiomes were more abundant in HR samples as compared to others. The high prevalence of functions associated with rhizobiomes in the tomato rhizosphere indicates that more research can be is justified carried out to establish the functional genes associated with the rhizobiomes of tomato plants. Therefore, this research proffers a better knowledge of the activities and functional diversity of microbial communities in tomato rhizosphere soils.